Diversity in Learning System: the Mnemonic Brain Science techniques as a multi dimensional Study approach - Vinod Sharma, (The Bioscan, 2026)
This new time is considered to be the new world of globalization, telecommunication and digital technology and scientific learning. These advancements in science, information and technology have proved to be a big change in many fields (for example – electronic gadgets like mobile phones, computers etc.) and have also increased in the complexities of life (for example – internet addiction, mobile phone addiction etc.)